The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1007/bf00151318
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of the H? emission in solar prominences

Abstract: The time dependence of Doppler shift and line-center intensity is simultaneously observed for the Hc~ emission of three solar prominences, each one during about two hours. Doppler oscillations with periods near one hour and amplitudes between 1 and 2 km s ~ are conspicuously visible in the recordings of all three prominences. Fourier analysis yields periods of 50, 60, and 64 min, as well as slight indications of short periods near 3 and 5 rain. No oscillations are found in the line-center brightness.The time v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
3
24
0
Order By: Relevance
“…At the outer penumbral boundary we find an abrupt drop of the flow velocities which agrees well with findings of e.g. Wiehr & Balthasar (1989), Title et al (1993), Wiehr & Degenhardt (1994), and Balthasar et al (1996). At the center side parts of the penumbrae the line-of-sight velocities become even negative in the deepest probed photospheric layers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the outer penumbral boundary we find an abrupt drop of the flow velocities which agrees well with findings of e.g. Wiehr & Balthasar (1989), Title et al (1993), Wiehr & Degenhardt (1994), and Balthasar et al (1996). At the center side parts of the penumbrae the line-of-sight velocities become even negative in the deepest probed photospheric layers.…”
Section: Discussionsupporting
confidence: 92%
“…Wiehr & Balthasar 1989;Title et al 1993;Wiehr & Degenhardt 1994;Balthasar et al 1996) have found an abrupt drop of the flow velocity whereas others (Alissandrakis et al 1988;Börner & Kneer 1992;Rimmele 1995b) have found a continuation of the flow beyond the outer penumbral boundary. Solanki et al (1994) have found a sharp drop of the Evershed flow in the low photosphere but a continuation of it in the higher so-called superpenumbral canopy.…”
Section: Introductionmentioning
confidence: 97%
“…Observational evidence of the time damping of small amplitude oscillations in prominences has been reported by Landman (1977), Tsubaki & Takeuchi (1986), Tsubaki (1988), Wiehr et al (1989), Molowny-Horas et al (1999), Terradas et al (2002), Lin (2004), Berger et al (2008) and Ning et al (2009a,b). MolownyHoras et al (1999) and Terradas et al (2002) studied twodimensional time series from a quiescent prominence and found that oscillations detected in large areas of the prominence were typically damped after 2−3 periods.…”
Section: Introductionmentioning
confidence: 84%
“…Landman et al 1997;Tsubaki & Takeuchi 1986;Wiehr et al 1989;Molowny-Horas et al 1999;Terradas et al 2002). This is then interpreted as a signature of wave damping by some as yet unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%